2006
DOI: 10.1097/01.prs.0000225430.42531.c2
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Science of Wound Healing

Abstract: Understanding wound healing today involves much more than simply stating that there are three phases: "inflammation, proliferation, and maturation." Wound healing is a complex series of reactions and interactions among cells and "mediators." Each year, new mediators are discovered and our understanding of inflammatory mediators and cellular interactions grows. This article will attempt to provide a concise report of the current literature on wound healing by first reviewing the phases of wound healing followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
1,022
0
109

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,261 publications
(1,161 citation statements)
references
References 115 publications
30
1,022
0
109
Order By: Relevance
“…2 We have observed that wounded skin can generate 14S,21R-diHDHA. 8,16 Several kinds of cells contribute to wound healing.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…2 We have observed that wounded skin can generate 14S,21R-diHDHA. 8,16 Several kinds of cells contribute to wound healing.…”
Section: Discussionmentioning
confidence: 91%
“…These data suggest that macrophages produce 14S,21R-diHDHA in wounds, especially at days 2 to 4 after wounding, when macrophages are the major leukocytes in wounds. 2 These results motivated us to further study the relation of decreased generation of 14S,21R-diHDHA to impaired prohealing functions of diabetic macrophages.…”
Section: S21r-dihdha Formation Is Decreased In Macrophages Of Diabmentioning
confidence: 98%
See 3 more Smart Citations